2006
DOI: 10.1093/eurheartj/ehi813
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and reversible cardiac dysfunction among amateur marathon runners

Abstract: Marathon running leads to transient systolic and more persistent diastolic dysfunction of both the LV and the RV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
134
8
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 28 publications
18
134
8
2
Order By: Relevance
“…Normal values and measurement variability data for this imaging modality have recently been published (18,42). Several recent studies have characterized resting LV strain and the impact of a single exercise session on LV strain in trained athletes (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Normal values and measurement variability data for this imaging modality have recently been published (18,42). Several recent studies have characterized resting LV strain and the impact of a single exercise session on LV strain in trained athletes (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac function has also been assessed using echocardiography and a global decrease in both systolic and diastolic RV (Neilan et al, 2006;Poh et al, 2008) and LV (Banks et al, 2011;George et al, 2009) function in recovery from prolonged endurance exercise reported in conjunction with the acute structural adaptations. The right-sided ECG changes evident in the current study may represent an electrical adaptation linked to these structural and functional changes and provide further insight into the acute electrical adaptations in response to a bout of ultra-endurance exercise.…”
Section: Standard 12 Lead Ecgmentioning
confidence: 99%
“…Understanding ethnic differences and similarities is important for understanding cardiovascular disease experiences among Indigenous populations. Longitudinal strain is a correlate of LV contractility and indicates regional myocardial dysfunction and longitudinal and circumferential strains are prognostic of cardiovascular events and survival [4345]. Further, elastance and arterial–ventricular coupling provide insight into the interaction between the arterial system and the LV, evaluating stroke work and energetic efficiency and providing indications of atherosclerotic heart disease [46].…”
Section: Discussionmentioning
confidence: 99%